Perancangan dan Pengembangan Video Dokumenter Almanac Chinese Dengan Menggunakan Motion Graphic - Tony Wibowo; Tony Jack Tan Ding (Universitas Internasional Batam, 2021)
The Chinese almanac is a traditional asset that has been passed down from China time to time. The contents of the Chinese almanac also cover a broad range of natural phenomena that humans could benefit from in everyday life. However, there aren’t a lot of people who understand the meaning behind of using Chinese almanacs. Even the usage of Chinese almanacs was also rarely seen in Chinese nowadays, especially in modern times. With this research of creating a documentary video of Chinese Almanac using motion graphics, this video can provide more information and educate the audience about Chinese Almanac. Using the method of MDLC as well as motion graphics in documentary videos, information can be conveyed creatively and attractively for public viewing. The finished results of this research are so that the people can appreciate and get a closer look about the culture of Chinese Almanac.